Staged release type rigid-flexible composite nerve conduit as well as preparation and application thereof
By designing a staged release-type rigid-flexible composite nerve catheter, using the combination of polymer nanofibers and multi-stage hydrogels, the space-time and controllable delivery of anti-inflammatory substances and growth factors is achieved, solving the problem that existing materials cannot regulate the microenvironment of spinal cord injury in stages, and promoting functional recovery after spinal cord injury.
Patent Information
- Application Number
- CN202311073244.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-24
Smart Images

Figure CN119499456A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomaterials, and in particular relates to a staged-release rigid-flexible composite nerve conduit, a preparation method and an application thereof. Background Art
[0002] Spinal cord injury caused by mechanical damage, disease, etc. is a serious trauma that occurs in the central nervous system. Clinical manifestations include loss of sensation below the damaged spinal cord segment, motor ability and sphincter dysfunction, etc., with extremely high disability and mortality rates. Spinal cord transection injury is the most harmful injury among spinal cord injuries, and the repair of spinal cord transection has become a major medical problem in the field of trauma repair. At present, clinical treatment methods mainly include decompression surgery and drug therapy, but these treatment methods often have a single effect and a short duration of action and cannot meet the requirements of the regenerative microenvironment at various stages after spinal cord injury, and are sometimes accompanied by serious secondary injuries and sequelae. In order to solve the above problems, it is necessary to start from the mechanism of spinal cord injury and design appropriate repair materials according to the needs.
[0003] Spinal cord injury is divided into two processes: primary injury and secondary injury. In the early stage of secondary injury, an inflammatory microenvironment will be formed in the injured area, triggering a large number of cell death, resulting in a large reduction in the cells secreting growth factors in the injured area; in the middle and late stages of secondary injury, due to the lack of growth factors in the microenvironment, the differentiation of neural stem cells into neurons is inhibited, and the regenerated axons cannot pass through the injured area to establish neural connections with the descending fiber bundles, thus making it impossible to achieve functional recovery. Current research on biomaterials applied to the spinal cord focuses on rebuilding a microenvironment suitable for repair after spinal cord injury. However, current material design can only regulate the microenvironment at a specific stage after spinal cord injury, and cannot achieve stage-by-stage regulation of the microenvironment to adapt to the regeneration needs of each stage of injury. For example, the research of Shen H, Liao S, et al. (Shen H, Xu B, Yang C, et al. A DAMP-scavenging, IL-10-releasing hydrogel promotes neural regeneration and motor function recovery after spinal cord injury [J]. Biomaterials, 2022, 280: 121279; Liao S, Liu Y, Kong Y, et al. A bionic multichannel nanofiber conduit carrying Tubastatin A for repairing injured spinal cord [J]. Materials Today Bio, 2022, 17: 100454). Summary of the Invention
[0004] The present invention provides a staged-release rigid-flexible composite nerve conduit, comprising a polymer nanofiber nerve conduit and a multi-segment hydrogel. The polymer nanofiber nerve conduit includes an inner layer and an outer layer. The inner layer is a unidirectional, orderly arranged fiber layer with core-shell structured nanoparticles deposited on the surface, wherein the shell layer is a bioactive substance and the core layer is a growth factor. The outer layer structure is a randomly arranged polymer fiber layer. The multi-segment hydrogel is a modified biomacromolecule with different cross-linking degrees, comprising short segments and long segments. The short segment hydrogel has a lower degree of cross-linking and contains anti-inflammatory drugs dispersed inside. It will be the first to rapidly degrade in the body and is used for regulating the early inflammatory response of spinal cord injury. The long segment hydrogel has a higher degree of cross-linking and contains growth factors dispersed inside. It will then slowly degrade in the body and is used for tissue regeneration after spinal cord injury.
[0005] The present invention regulates the topological structure and gradient structure of spun polymer fibers and combines them with a multi-segment hydrogel delivery system to achieve spatiotemporal controllable delivery of multiple anti-inflammatory substances and growth factors, regulate the microenvironment of early spinal cord injury, mediate cell migration and axon extension in the middle stage of spinal cord repair, and promote neural connection reconstruction and functional recovery in the late stage of spinal cord injury, providing a new approach and method for the design of spinal cord injury repair materials.
[0006] One of the objectives of the present invention is to provide a staged-release rigid-flexible composite nerve conduit, which has a polymer fiber membrane as the tube wall and a multi-segment hydrogel as the inner core. The inner wall of the polymer fiber membrane is deposited with bioactive material particles containing growth factors, and the multi-segment hydrogel includes short-segment hydrogels containing anti-inflammatory substances and long-segment hydrogels containing growth factors.
[0007] In the staged release rigid-flexible composite nerve conduit provided by the present invention:
[0008] The polymer fiber membrane is a double-layer nanofiber membrane structure, wherein the inner layer is a unidirectional orderly arranged nanofiber membrane, and the outer layer is a randomly arranged nanofiber membrane;
[0009] The polymer in the polymer fiber is selected from at least one of degradable aliphatic polyesters, preferably at least one of polylactic acid, polycaprolactone, polylactic acid-glycolic acid copolymer, and polylactic acid-glycolic acid-caprolactone copolymer;
[0010] The anti-inflammatory substance is selected from at least one of catalase, superoxide dismutase, interleukin, and reducing molecules;
[0011] The growth factor has a repair-promoting effect. Preferably, the growth factor is selected from at least one of vascular endothelial growth factor, fibroblast growth factor, epidermal growth factor, brain-derived neurotrophic factor, neurotrophic factor-3, glial cell-derived neurotrophic factor, ciliary neurotrophic factor, and nerve growth factor. The bioactive substance particles and the long hydrogel may use the same or different growth factors, or one or more growth factors may be used.
[0012] The hydrogel precursor compound used in the hydrogel is selected from at least one of acrylated biomacromolecules, preferably at least one of methacrylated gelatin, methacrylated hyaluronic acid, methacrylated silk fibroin, methacrylated chitosan, and methacrylated sodium alginate; wherein the short-segment hydrogel and the long-segment hydrogel use the same hydrogel precursor compound;
[0013] The bioactive substance particles containing growth factors are of a core-shell structure, wherein the shell layer is the bioactive substance and the core layer is the growth factor;
[0014] The bioactive substance simulates the composition of the extracellular matrix. Specifically, the bioactive substance is selected from at least one of protein compounds, preferably at least one of collagen, laminin, fibronectin, and collagen;
[0015] The thickness of the polymer fiber membrane tube wall is 50 to 800 μm, preferably 100 to 500 μm;
[0016] The length ratio of the short hydrogel to the long hydrogel is 1:(1.5-10), preferably 1:(1.5-5); the length of the hydrogel can be adjusted by the volume of the injected hydrogel precursor solution;
[0017] The cross-linking degree of the short-segment hydrogel is lower than that of the long-segment hydrogel, and the cross-linking degree of the hydrogel can be obtained by adjusting different cross-linking times.
[0018] A second object of the present invention is to provide a method for preparing the above-mentioned phased-release rigid-flexible composite nerve conduit, comprising: cross-linking a hydrogel precursor solution containing an anti-inflammatory substance and a hydrogel precursor solution containing a growth factor by ultraviolet light to obtain multiple hydrogel segments, and then wrapping the multiple hydrogel segments with a polymer fiber membrane having an inner layer deposited with bioactive substance particles containing growth factors, thereby obtaining the phased-release rigid-flexible composite nerve conduit.
[0019] The present invention provides a method for preparing a staged-release rigid-flexible composite nerve conduit, which specifically comprises the following steps:
[0020] Step (1) electrospinning the polymer solution A to obtain a double-layer polymer fiber membrane;
[0021] Step (2) using coaxial electrostatic spraying to spray the growth factor solution B and the bioactive substance solution C onto the inner layer of the polymer fiber membrane obtained in step (1) to prepare a polymer fiber membrane with gradient density deposition of bioactive substance particles;
[0022] Step (3) mixing the growth factor solution D and the anti-inflammatory substance solution E with an initiator to obtain an initiator solution F and an initiator solution G, and then adding a hydrogel precursor compound to obtain a hydrogel precursor solution H and a hydrogel precursor solution I;
[0023] Step (4) injecting the hydrogel precursor solution H into the mold, crosslinking it with ultraviolet light, and then continuously injecting the hydrogel precursor solution I, crosslinking it with ultraviolet light, to obtain a multi-segment hydrogel;
[0024] In step (5), the inner layer of the polymer fiber membrane with gradient density deposited bioactive material particles obtained in step (2) is contacted with the multi-segment hydrogel obtained in step (4), and wrapped into a tube, and finally bonded with polymer solution A to obtain the staged release rigid-flexible composite nerve conduit.
[0025] In step (1) of the above preparation method:
[0026] The solvent in the polymer solution A is selected from at least one of hexafluoroisopropanol, trifluoroethanol, chloroform, methanol, dichloromethane, and N,N'-dimethylformamide;
[0027] The mass percentage concentration of the polymer solution A is 5 to 25%, preferably 8 to 15%;
[0028] The electrospinning includes: performing uniaxial electrospinning on the polymer solution A, using a roller or a U-shaped groove as a receiver, the spinning solution flow rate is 0.1 to 3 mL / h, the voltage is 10 to 20 kV, and the receiving distance is 10 to 20 cm; preferably, when the electrospinning uses a roller as a receiver, the high-speed rotating roller is first used as the receiver for spinning for 2 to 10 hours to obtain a unidirectional ordered fiber membrane, and then the roller speed is reduced for spinning for 2 to 10 hours; or, when the electrospinning uses a U-shaped groove as a receiver, the U-shaped groove is first used as the receiver for spinning for 2 to 10 hours to obtain a unidirectional ordered fiber membrane, and then the U-shaped groove is removed, and the obtained unidirectional ordered fiber membrane is used as a collector for spinning for 2 to 10 hours.
[0029] In step (2) of the above preparation method:
[0030] The solvent in the growth factor solution B is selected from at least one of phosphate buffered saline (PBS), water, ethanol, polyvinyl alcohol, polyacrylamide, and polyacrylic acid;
[0031] The concentration of the growth factor solution B is 0.1 μg / mL to 5 mg / mL, preferably 1 μg / mL to 1 mg / mL;
[0032] The solvent in the bioactive substance solution C is selected from at least one of hydrochloric acid, acetic acid aqueous solution, ethyl acetate, glycerol, trifluoroethanol, and hexafluoroisopropanol;
[0033] The concentration of the bioactive substance solution C is 1 to 50 mg / mL, preferably 10 to 30 mg / mL;
[0034] The coaxial electrostatic spraying comprises: using a mask mode to perform electrostatic spraying with a gradient concentration, regulating the electrostatic spraying time at different positions on the fiber surface by moving the mask, and depositing bioactive material particles in a manner that the particle density increases gradiently along the direction of orderly arrangement of the fibers. Specifically, using a mask mode to deposit bioactive material particles in a manner that the particle density increases gradiently along the direction of orderly arrangement of the fibers, injecting a bioactive material solution C into a shell layer syringe, and injecting a growth factor solution B into a core layer syringe, the inner layer of the polymer fiber membrane obtained in step (1) serves as a receiver, the flow rate of the shell layer electrospray solution is 0.5 to 3 mL / h, the flow rate of the core layer electrospray solution is 0.2 to 1 mL / h, the voltage is 10 to 20 kV, the receiving distance is 10 to 20 cm, and the electrostatic spraying time is 1 to 60 min; preferably, the flow rate of the shell layer electrospray solution is higher than the flow rate of the core layer electrospray solution; the density of the growth factor nanoparticles in the obtained polymer fiber membrane increases gradiently along the direction of fiber arrangement;
[0035] The polymer fiber membrane obtained after electrostatic spraying needs to be freed of solvent. The solvent removal can be removed by a common solvent removal method or by allowing it to evaporate, such as placing it in a fume hood at room temperature for 2-7 days. After the solvent is removed, the membrane is packaged and disinfected.
[0036] In step (3) of the above preparation method:
[0037] The solvent in the growth factor solution D is selected from at least one of phosphate buffered saline (PBS), water, ethanol, polyvinyl alcohol, polyacrylamide, and polyacrylic acid; the concentration of the growth factor solution D is 0.1 μg / mL to 5 mg / mL, preferably 1 μg / mL to 1 mg / mL;
[0038] The solvent in the anti-inflammatory substance solution E is selected from at least one of phosphate buffered saline (PBS), water, chloroform, glycerol, trifluoroethanol, and hexafluoroisopropanol; the concentration of the anti-inflammatory substance solution E is 1 μg / mL to 5 mg / mL, preferably 0.1 to 2 mg / mL;
[0039] The initiator in the initiator solution F and the initiator in the initiator solution G are independently selected from at least one of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959), lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP), and ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L);
[0040] The mass percentage of the initiator in the initiator solution F is 0.1 to 0.5%, preferably 0.15 to 0.3%; the mass percentage of the initiator in the initiator solution G is 0.1 to 0.5%, preferably 0.15 to 0.3%;
[0041] The mass percentage of the hydrogel precursor compound in the hydrogel precursor solution H is 5 to 15%, preferably 8 to 12%; the mass percentage of the hydrogel precursor compound in the hydrogel precursor solution I is 5 to 15%, preferably 8 to 12%;
[0042] In step (3), the growth factor solution D and the anti-inflammatory substance solution E are mixed with the initiator at 37°C in the dark. After thorough oscillation and mixing, initiator solution F and initiator solution G are obtained respectively. The mixture is heated to 37°C in a constant temperature water bath in the dark, and then the hydrogel precursor compound is added to the initiator solution. The mixture is thoroughly oscillated and mixed at 37°C to obtain a hydrogel precursor solution.
[0043] In step (4) of the above preparation method:
[0044] The mold is a tubular mold; the conditions for UV crosslinking are: a crosslinking temperature of 18 to 37° C., preferably 20 to 30° C.; a crosslinking time of 4 to 60 seconds, preferably 4 to 30 seconds;
[0045] UV crosslinking includes: first, heating the hydrogel precursor solution H and the hydrogel precursor solution I to 37°C in a constant temperature water bath in the dark, then adding the hydrogel precursor solution H into a syringe and quickly injecting it into a tubular mold through a 0.22 μm filter, crosslinking the hydrogel precursor solution in the mold under light, and the photocrosslinking time is 4 to 60 seconds. Finally, adding the hydrogel precursor solution I into a syringe and quickly passing it through a 0.22 μm filter to fill the same tubular mold, and crosslinking the hydrogel and the hydrogel precursor solution in the mold again under light, and the photocrosslinking time is 4 to 60 seconds. Hydrogels with different crosslinking degrees can be obtained by adjusting the crosslinking time.
[0046] A third object of the present invention is to provide the above-mentioned phased-release rigid-flexible composite nerve conduit or the phased-release rigid-flexible composite nerve conduit obtained by the above-mentioned preparation method, and its application in bio-based repair materials.
[0047] When the rigid-flexible composite nerve conduit provided by the present invention, which can release anti-inflammatory substances and growth factors in stages, is used as a spinal cord injury repair material, the spatiotemporal controllable delivery of anti-inflammatory substances and growth factors in the hydrogel is achieved by using multiple hydrogels with different degradation times, matching the process of spinal cord injury repair. The continuous degradation and release of the loaded factors by the hydrogel solves the problem of short drug action time. Among them, the short-segment hydrogel loaded with anti-inflammatory drugs will degrade and release anti-inflammatory drugs in the early stage of spinal cord injury to regulate the inflammatory microenvironment and provide a suitable microenvironment for subsequent repair. Subsequently, the long-segment hydrogel loaded with multiple growth factors will degrade in the middle and late stages of spinal cord injury to supplement the damaged area with multiple growth factors, promote axon extension in the damaged area, and establish neural connections with the descending fiber bundles. In addition, while the spatiotemporal controllable delivery of multiple factors can achieve the repair of spinal cord injury at various stages, physical guidance will also be provided for axon extension by constructing nanofibers with a unidirectional ordered topological structure, combining the gradient density signal of surface bioactive material particles, and introducing pro-repair growth factors. The rigid-flexible composite nerve conduit capable of releasing anti-inflammatory substances and growth factors in stages can better meet the repair needs of each stage after spinal cord injury. After the spinal cord injury repair process is completed, the nerve conduit can be degraded and metabolized by the body.
[0048] The present invention can achieve the following beneficial effects:
[0049] 1. The inner surface of the nanofiber conduit used in the present invention realizes the efficient integration of multiple induction signals such as ordered topological structure and growth factor gradient density signal;
[0050] 2. The fiber conduit portion of the rigid-flexible composite nerve conduit not only stabilizes the hydrogel morphology, but also, after the hydrogel degrades, the inner conduit layer, due to its unidirectional, ordered fiber arrangement and the gradient-deposited bioactive material particles, can still promote axonal extension and cell migration for a long time. The randomly arranged fibers in the outer layer provide sufficient elasticity and toughness to meet the needs of spinal mobility during and after surgery.
[0051] 3. The rigid-flexible composite nerve conduit used in the present invention, which can release anti-inflammatory substances and growth factors in stages, has excellent biocompatibility and degradation properties. It can provide the required microenvironment for each stage of injury through the spatiotemporal controllable delivery of different factors, promoting axonal extension and the reconstruction of neural connections.
[0052] 4. The rigid-flexible composite nerve conduit of the present invention, which can release anti-inflammatory substances and growth factors in stages, has the ability to release multiple factors in a controlled manner in time and space, meeting the microenvironment required at each stage of spinal cord injury. It has the functions of promoting cell migration, axon extension, and neural connection reconstruction. It also has a biomimetic structure similar to the extracellular matrix (ECM) and good biocompatibility, and is expected to become an ideal spinal cord injury repair material.
[0053] 5. This invention targets spinal cord transection injuries and designs a nerve conduit to connect and bridge the two ends of the injury. The rigid-flexible composite design provides a good environment for nerve regeneration in terms of matrix elasticity and toughness.
[0054] 6. The present invention adopts a multi-segment hydrogel spatiotemporal controllable delivery strategy. Short-segment hydrogels are degraded in the early stage of injury to release anti-inflammatory substances to regulate the injury microenvironment, provide a suitable microenvironment for subsequent repair, and continuously replenish growth factors to the injured area through the degradation of long-segment hydrogels in the middle and late stages of injury, promote axon extension and establish neural connections with descending fiber bundles, which can effectively promote the functional recovery of the damaged spinal cord. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 It is a schematic diagram of a rigid-flexible composite nerve conduit with staged release formed by wrapping a multi-segment hydrogel loaded with anti-inflammatory drugs and growth factors with a polymer fiber membrane having an inner layer deposited with growth factor particles obtained in Examples 1 to 4.
[0056] Figure 2 : is a SEM photo of the polymer fiber membrane before and after gradient density deposition of growth factor particles prepared in Example 1. Figure 2 It can be seen that the polymer fiber membrane has an obvious double-layer structure, the inner layer fibers are unidirectionally arranged in an orderly structure, the outer layer is a randomly arranged structure, and the bioactive substance particles are densely deposited on the surface of the ordered fibers in the inner layer.
[0057] Figure 3 This is a SEM photograph of the polymer fiber membrane with gradient density deposited growth factor particles obtained in Example 1 being wound into a fiber conduit without a mold.
[0058] Figure 4 : is the SEM photo of the short segment hydrogel and the long segment hydrogel prepared in Example 1. Figure 4 It can be seen that the hydrogel loaded with anti-inflammatory drugs has a larger pore size and a correspondingly faster degradation rate, while the hydrogel loaded with growth factors has a smaller pore size and a correspondingly slower degradation rate. Due to the different degradation rates of different hydrogel segments, the loaded drugs can be delivered in a controlled manner in time and space.
[0059] Figure 5 The results of cell proliferation tests are shown for the blank group, the polymer fiber membrane with pure collagen particles deposited at gradient density in comparative example 1, the polymer fiber membrane with pure collagen particles deposited at uniform density in comparative example 2, the polymer fiber membrane without bioactive material particles deposited in comparative example 3, and the polymer fiber membrane with growth factor particles deposited at gradient density in example 1. The horizontal axis represents the number of days of cell culture and the vertical axis represents the absorbance value. Figure 5 It can be seen that the density gradient signal and the deposition of growth factors on the fiber membrane of Example 1 have a promoting effect on cell proliferation. DETAILED DESCRIPTION
[0060] The present invention will be described in detail below with reference to specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and are not to be construed as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made by those skilled in the art to the present invention based on the contents of the present invention still fall within the scope of protection of the present invention.
[0061] The test instruments and test conditions used in the examples are as follows:
[0062] Electrospinning equipment: Model: TEADFS-103, Beijing Xinrui Baina Technology Co., Ltd. (roller as receiver)
[0063] Electrospinning equipment: Model: NANO 01, MECC Co., Ltd., Japan; (U-shaped groove is the receiver)
[0064] Electrostatic spray equipment: Model: NANO 01, Japan MECC Co., Ltd.
[0065] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0066] The degradable aliphatic polyester raw materials used in the examples were purchased from Sigma Reagent Company, organic solvents were purchased from Aladdin Company, growth factors were purchased from Thermo Fisher Scientific Company, modified biomacromolecules and initiators were purchased from EFL Company, and anti-inflammatory drugs were purchased from Yuanye Company.
[0067] Example 1
[0068] Step (1) adding polycaprolactone to a mixed solution of dichloromethane and N,N-dimethylformamide (dichloromethane and N,N-dimethylformamide in a volume ratio of 4:1), and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 10%; performing uniaxial electrospinning with solution A at a flow rate of 1 mL / h, a voltage of 16 kV, a receiving distance of 15 cm, and a high-speed rotating roller as a receiver for 5 hours to obtain unidirectional ordered fibers, then gradually reducing the roller speed, and continuing to collect randomly arranged fibers for 5 hours to obtain a double-layer polymer fiber membrane; and placing the polymer fiber membrane in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;
[0069] Step (2) dissolving neurotrophic factor-3 in PBS and mixing thoroughly to obtain a growth factor solution B with a concentration of 100 μg / mL; dissolving collagen in an acetic acid aqueous solution with a volume fraction of 70% and mixing thoroughly to obtain a bioactive substance solution C with a concentration of 20 mg / mL; replacing the electrospray liquid with growth factor solution B and bioactive substance solution C, replacing the uniaxial spinning needle with a coaxial needle, injecting the growth factor solution B into the core layer syringe, and injecting the bioactive substance solution C into the shell layer syringe; the inner layer of the polymer fiber membrane obtained in step (1) is used as a receiver, and coaxial electrostatic spraying is performed, using a mask strategy to deposit bioactive substance particles with a particle density gradient increasing along the unidirectional orderly arrangement direction, the flow rate of growth factor solution B is 0.5 mL / h, the flow rate of bioactive substance solution C is 1.5 mL / h, the voltage is 20 kV, and the electrostatic spraying is performed for 30 minutes to deposit the growth factor particles with a gradient density on the inner surface of the polymer fiber membrane;
[0070] Step (3) dissolving epidermal growth factor, glial cell line-derived neurotrophic factor, and neurotrophic factor-3 in PBS and mixing them thoroughly to obtain a growth factor solution D with a concentration of 100 μg / mL for each growth factor; adding catalase and superoxide dismutase to PBS and mixing them thoroughly to obtain an anti-inflammatory substance solution E with a concentration of 100 μg / mL; adding LAP to the growth factor solution D and the anti-inflammatory substance solution E, respectively, and shaking and mixing them in the dark at 37°C to obtain an initiator solution F and an initiator solution G with a mass fraction of 0.25%, and adding methacrylated gelatin to the initiator solution F and the initiator solution G, respectively, and shaking and mixing them in the dark at 37°C to obtain a hydrogel precursor solution H and a hydrogel precursor solution I with a mass fraction of 10%;
[0071] Step (4) heating the hydrogel precursor solution H and the hydrogel precursor solution I obtained in step (3) to 37° C., then adding the hydrogel precursor solution H into a syringe and rapidly injecting 15 μL into a tubular mold through a 0.22 μm filter, cross-linking the hydrogel precursor solution in the mold under 405 nm blue light, and the photocrosslinking time is 8 s. Finally, adding the hydrogel precursor solution I into a syringe and rapidly injecting 5 μL into the same tubular mold through a 0.22 μm filter, cross-linking the hydrogel and the hydrogel precursor solution in the mold again under 405 nm blue light, and the photocrosslinking time is 8 s, to obtain a multi-segment filled hydrogel, wherein the ratio of the length of the short segment to the long segment is 1:3;
[0072] In step (5), the multi-segment filled hydrogel obtained in step (4) is used as a mold, the inner layer of the polymer fiber membrane with the gradient density deposited growth factor particles obtained in step (1) is contacted with the hydrogel and wrapped into a tube, polymer solution A is applied to the adhesion at room temperature, and after adhesion, it is dried in a clean bench, and finally demolded to obtain a rigid-flexible composite nerve conduit that can release anti-inflammatory substances and growth factors in stages.
[0073] Example 2
[0074] Step (1) adding polylactic acid to dichloromethane, and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 10%; performing uniaxial electrospinning with solution A at a flow rate of 1 mL / h, a voltage of 16 kV, a receiving distance of 15 cm, and a high-speed rotating roller as a receiver for 5 hours to obtain unidirectional ordered fibers, then gradually reducing the roller speed and continuing to collect randomly arranged fibers for 5 hours to obtain a double-layer polymer fiber membrane; and placing the polymer fiber membrane in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;
[0075] Step (2) dissolving nerve growth factor in PBS and mixing thoroughly to obtain a growth factor solution B with a concentration of 100 μg / mL; dissolving collagen in an acetic acid aqueous solution with a volume fraction of 70% and mixing thoroughly to obtain a bioactive substance solution C with a concentration of 20 mg / mL; replacing the electrospray liquid with growth factor solution B and bioactive substance solution C, replacing the uniaxial spinning needle with a coaxial needle, injecting the growth factor solution B into the core layer syringe, and injecting the bioactive substance solution C into the shell layer syringe; the inner layer of the polymer fiber membrane obtained in step (1) is used as a receiver, and coaxial electrostatic spraying is performed, using a mask strategy to deposit bioactive substance particles with a particle density gradient increasing along the unidirectional orderly arrangement direction, the flow rate of growth factor solution B is 0.5 mL / h, the flow rate of bioactive substance solution C is 1.5 mL / h, the voltage is 20 kV, and the electrostatic spraying is performed for 10 minutes to obtain gradient density deposited growth factor particles on the inner surface of the polymer fiber membrane;
[0076] Step (3) dissolving recombinant human basic fibroblast growth factor, epidermal growth factor, and brain-derived neurotrophic factor in PBS and mixing them thoroughly to obtain a growth factor solution D with a concentration of 100 μg / mL for each growth factor; adding IL-10 and IL-4 to PBS and mixing them thoroughly to obtain an anti-inflammatory substance solution E with a concentration of 100 μg / mL; adding LAP to the growth factor solution D and the anti-inflammatory substance solution E, respectively, and shaking and mixing them in the dark at 37°C to obtain an initiator solution F and an initiator solution G with a mass fraction of 0.25%, and adding methacrylated gelatin to the initiator solution F and the initiator solution G, respectively, and shaking and mixing them in the dark at 37°C to obtain a hydrogel precursor solution H and a hydrogel precursor solution I with a mass fraction of 10%;
[0077] Step (4) heating the hydrogel precursor solution H and the hydrogel precursor solution I obtained in step (3) to 37° C., then adding the hydrogel precursor solution H into a syringe and rapidly injecting 16 μL into a tubular mold through a 0.22 μm filter, cross-linking the hydrogel precursor solution in the mold under 405 nm blue light, and the photocrosslinking time is 8 s. Finally, adding the hydrogel precursor solution I into a syringe and rapidly injecting 4 μL into the same tubular mold through a 0.22 μm filter, cross-linking the hydrogel and the hydrogel precursor solution in the mold again under 405 nm blue light, and the photocrosslinking time is 8 s, to obtain a multi-segment filled hydrogel, wherein the ratio of the length of the short segment to the long segment is 1:4;
[0078] In step (5), the multi-segment filled hydrogel obtained in step (4) is used as a mold, the inner layer of the polymer fiber membrane with the gradient density deposited growth factor particles obtained in step (1) is contacted with the hydrogel and wrapped into a tube, polymer solution A is applied to the adhesion at room temperature, and after adhesion, it is dried in a clean bench, and finally demolded to obtain a rigid-flexible composite nerve conduit that can release anti-inflammatory substances and growth factors in stages.
[0079] Example 3
[0080] Step (1) preparing a polylactic acid-co-glycolic acid (PLGA) solution in a volume ratio of dichloromethane to N,N-dimethylformamide = 4:1, and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 10%; performing uniaxial electrospinning with the solution A at a flow rate of 1 mL / h, a voltage of 16 kV, a receiving distance of 15 cm, and a high-speed rotating roller as a receiver for 5 hours to obtain unidirectional ordered fibers, then gradually reducing the roller speed and continuing to collect randomly arranged fibers for 5 hours to obtain a double-layer polymer fiber membrane; and placing the polymer fiber membrane in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;
[0081] Step (2) dissolving brain-derived neurotrophic factor in PBS and mixing thoroughly to obtain a growth factor solution B with a concentration of 100 μg / mL; dissolving collagen in an acetic acid aqueous solution with a volume fraction of 70% and mixing thoroughly to obtain a bioactive substance solution C with a concentration of 20 mg / mL; replacing the electrospray liquid with growth factor solution B and bioactive substance solution C, replacing the uniaxial spinning needle with a coaxial needle, injecting the growth factor solution B into the core layer syringe, and injecting the bioactive substance solution C into the shell layer syringe; the inner layer of the polymer fiber membrane obtained in step (1) is used as a receiver, and coaxial electrostatic spraying is performed, using a mask strategy to deposit bioactive substance particles with a particle density gradient increasing along the unidirectional orderly arrangement direction, the flow rate of growth factor solution B is 0.5 mL / h, the flow rate of bioactive substance solution C is 1.5 mL / h, the voltage is 20 kV, and the electrostatic spraying is performed for 30 minutes, and the growth factor particles are deposited on the inner surface of the polymer fiber membrane with a gradient density;
[0082] Step (3) dissolving recombinant human basic fibroblast growth factor, nerve growth factor, and glial cell line-derived neurotrophic factor in PBS and mixing them thoroughly to obtain a growth factor solution D with a concentration of 100 μg / mL for each growth factor; adding curcumin and resveratrol to PBS and mixing them thoroughly to obtain an anti-inflammatory substance solution E with a concentration of 100 μg / mL; adding LAP to the growth factor solution D and the anti-inflammatory substance solution E, respectively, and shaking and mixing them in the dark at 37°C to obtain an initiator solution F and an initiator solution G with a mass fraction of 0.25%, and adding methacrylated gelatin to the initiator solution F and the initiator solution G, respectively, and shaking and mixing them in the dark at 37°C to obtain a hydrogel precursor solution H and a hydrogel precursor solution I with a mass fraction of 10%;
[0083] Step (4) heating the hydrogel precursor solution H and the hydrogel precursor solution I obtained in step (3) to 37° C., then adding the hydrogel precursor solution H into a syringe and rapidly injecting 12 μL into a tubular mold through a 0.22 μm filter, cross-linking the hydrogel precursor solution in the mold under 405 nm blue light, and the photocrosslinking time is 8 s. Finally, adding the hydrogel precursor solution I into a syringe and rapidly injecting 8 μL into the same tubular mold through a 0.22 μm filter, cross-linking the hydrogel and the hydrogel precursor solution in the mold again under 405 nm blue light, and the photocrosslinking time is 8 s, to obtain a multi-segment filled hydrogel, wherein the ratio of the length of the short segment to the long segment is 1:1.5;
[0084] In step (5), the multi-segment filled hydrogel obtained in step (4) is used as a mold, the inner layer of the polymer fiber membrane with the gradient density deposited growth factor particles obtained in step (1) is contacted with the hydrogel and wrapped into a tube, polymer solution A is applied to the adhesion at room temperature, and after adhesion, it is dried in a clean bench, and finally demolded to obtain a rigid-flexible composite nerve conduit that can release anti-inflammatory substances and growth factors in stages.
[0085] Example 4
[0086] Step (1) preparing a polylactic acid-co-glycolic acid (PLGA) solution in a volume ratio of dichloromethane:N,N-dimethylformamide=4:1, and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 12%; performing uniaxial electrospinning with solution A at a flow rate of 0.8 mL / h, a voltage of 15 kV, a receiving distance of 15 cm, and a U-shaped groove as a receiver for 6 hours to obtain a unidirectional ordered fiber membrane, then removing the U-shaped groove, and using the obtained unidirectional ordered fiber membrane as a collector to collect randomly arranged fibers for 6 hours to obtain a double-layer polymer fiber membrane; and placing the polymer fiber membrane in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;
[0087] Step (2) dissolving brain-derived neurotrophic factor in PBS and mixing thoroughly to obtain a growth factor solution B with a concentration of 150 μg / mL; dissolving collagen in an acetic acid aqueous solution with a volume fraction of 70% and mixing thoroughly to obtain a bioactive substance solution C with a concentration of 20 mg / mL; replacing the electrospray liquid with growth factor solution B and bioactive substance solution C, replacing the uniaxial spinning needle with a coaxial needle, injecting the growth factor solution B into the core layer syringe, and injecting the bioactive substance solution C into the shell layer syringe; the inner layer of the polymer fiber membrane obtained in step (1) is used as a receiver, and coaxial electrostatic spraying is performed, using a mask strategy to deposit bioactive substance particles with a particle density gradient increasing along the unidirectional orderly arrangement direction, the flow rate of the growth factor solution B is 0.8 mL / h, the flow rate of the bioactive substance solution C is 1.6 mL / h, the voltage is 18 kV, and the electrostatic spraying is performed for 10 minutes, and the growth factor particles are deposited on the inner surface of the polymer fiber membrane with a gradient density;
[0088] Step (3) dissolving vascular endothelial growth factor, nerve growth factor-3, and glial cell line-derived neurotrophic factor in PBS and mixing them thoroughly to obtain a growth factor solution D with a concentration of 150 μg / mL for each growth factor; adding curcumin and resveratrol to PBS and mixing them thoroughly to obtain an anti-inflammatory substance solution E with a concentration of 150 μg / mL; adding LAP to growth factor solution D and anti-inflammatory substance solution E, respectively, and shaking and mixing them in the dark at 37°C to obtain initiator solutions F and initiator solutions G with a mass fraction of 0.25%, and adding methacrylated gelatin to initiator solutions F and initiator solutions G, respectively, and shaking and mixing them in the dark at 37°C to obtain hydrogel precursor solutions H and hydrogel precursor solutions I with a mass fraction of 12%;
[0089] Step (4) heating the hydrogel precursor solution H and the hydrogel precursor solution I obtained in step (3) to 37° C., then adding the hydrogel precursor solution H into a syringe and rapidly injecting 18 μL into a tubular mold through a 0.22 μm filter, cross-linking the hydrogel precursor solution in the mold under 405 nm blue light, and the photocrosslinking time is 10 s. Finally, adding the hydrogel precursor solution I into a syringe and rapidly injecting 2 μL into the same tubular mold through a 0.22 μm filter, cross-linking the hydrogel and the hydrogel precursor solution in the mold again under 405 nm blue light, and the photocrosslinking time is 10 s, to obtain a multi-segment filled hydrogel, wherein the ratio of the length of the short segment to the long segment is 1:9;
[0090] In step (5), the multi-segment filled hydrogel obtained in step (4) is used as a mold, the inner layer of the polymer fiber membrane with the gradient density deposited growth factor particles obtained in step (1) is contacted with the hydrogel and wrapped into a tube, polymer solution A is applied to the adhesion at room temperature, and after adhesion, it is dried in a clean bench, and finally demolded to obtain a rigid-flexible composite nerve conduit that can release anti-inflammatory substances and growth factors in stages.
[0091] Comparative Example 1
[0092] Step (1) adding polycaprolactone to a mixed solution of dichloromethane and N,N-dimethylformamide (the volume ratio of dichloromethane to N,N-dimethylformamide is 4:1), and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 10%; performing uniaxial electrospinning with solution A at a flow rate of 1 mL / h, a voltage of 16 kV, a receiving distance of 15 cm, and a high-speed rotating roller as a receiver for 5 hours to obtain unidirectional ordered fibers, then gradually reducing the roller speed, and continuing to collect randomly arranged fibers for 5 hours to obtain a double-layer polymer fiber membrane; and placing the polymer fiber membrane in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;
[0093] In step (2), collagen is dissolved in an acetic acid aqueous solution with a volume fraction of 70%, and the solution is thoroughly mixed to obtain a bioactive substance solution C with a concentration of 20 mg / mL; the electrospray liquid is replaced with the bioactive substance solution C, and a uniaxial spinning needle is used to inject the bioactive substance solution into a syringe; the inner layer of the polymer fiber membrane obtained in step (1) is used as a receiver, and uniaxial electrostatic spraying is performed. A mask strategy is used to deposit bioactive substance particles with a particle density gradient increasing along the unidirectional orderly arrangement direction. The flow rate of the bioactive substance solution C is 1.5 mL / h, the voltage is 20 kV, and the electrostatic spraying is performed for 30 minutes, and pure collagen particles are deposited on the inner surface of the polymer fiber membrane with a gradient density.
[0094] The polymer fiber membrane prepared in this comparative example is the one corresponding to Example 1, with pure collagen particles deposited at a gradient density on the inner surface.
[0095] Comparative Example 2
[0096] Step (1) adding polycaprolactone to a mixed solution of dichloromethane and N,N-dimethylformamide (the volume ratio of dichloromethane to N,N-dimethylformamide is 4:1), and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 10%; performing uniaxial electrospinning with solution A at a flow rate of 1 mL / h, a voltage of 16 kV, a receiving distance of 15 cm, and a high-speed rotating roller as a receiver for 5 hours to obtain unidirectional ordered fibers, then gradually reducing the roller speed, and continuing to collect randomly arranged fibers for 5 hours to obtain a double-layer polymer fiber membrane; and placing the polymer fiber membrane in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;
[0097] In step (2), collagen is dissolved in an acetic acid aqueous solution with a volume fraction of 70%, and the solution is thoroughly mixed to obtain a bioactive substance solution C with a concentration of 20 mg / mL; the electrospray liquid is replaced with the bioactive substance solution C, and a uniaxial spinning needle is used to inject the bioactive substance solution C into a syringe; the inner layer of the polymer fiber membrane obtained in step (1) is used as a receiver, and uniaxial electrostatic spraying is performed to uniformly deposit bioactive substance particles. The flow rate of the bioactive substance solution C is 1.5 mL / h, the voltage is 20 kV, and the electrostatic spraying is performed for 30 minutes, and pure collagen particles are uniformly deposited on the inner surface of the polymer fiber membrane.
[0098] The polymer fiber membrane prepared in this comparative example is the one corresponding to Example 1, with pure collagen particles deposited at a uniform density on the inner surface.
[0099] Comparative Example 3
[0100] Step (1) adding polycaprolactone to a mixed solution of dichloromethane and N,N-dimethylformamide (the volume ratio of dichloromethane to N,N-dimethylformamide is 4:1), and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 10%; performing uniaxial electrospinning with solution A at a flow rate of 1 mL / h, a voltage of 16 kV, a receiving distance of 15 cm, and a high-speed rotating roller as a receiver for 5 hours to obtain unidirectional ordered fibers, then gradually reducing the roller speed, and continuing to collect randomly arranged fibers for 5 hours to obtain a double-layer polymer fiber membrane; and placing the polymer fiber membrane in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;
[0101] The polymer fiber membrane prepared in this comparative example is the one corresponding to Example 1, but without the bioactive material particles deposited on the inner surface.
[0102] Test example:
[0103] The cell proliferation test was performed using the CCK-8 method to verify the proliferation activity of cells on the polymer fiber membrane materials prepared in the examples and comparative examples.
[0104] Cut the UV-sterilized material into 1.5 cm diameter pieces and place them on the bottom of a 24-well plate. Use a 1.5 cm diameter ring that has been autoclaved and UV-sterilized to secure the material so that it is embedded in the bottom with the inner layer facing up. Soak the material in PBS buffer for 20 minutes in the well plate. Shake on a shaker to remove any surface residue. After shaking, discard the PBS and rinse twice with fresh PBS buffer. Rinse once with Schwann cell culture medium before use. Take Schwann cells that have grown to confluent on the bottom of a T25 culture flask and plate them. Take 1 mL of 0.25% pancreatic enzyme-EDTA solution and add it to a T25 culture flask full of Schwann cells. Incubate it in a 37°C cell culture incubator for 3 minutes. After taking it out, gently tap the side wall of the culture flask, add 3 mL of Schwann cell culture medium, mix it evenly, aspirate the liquid in the bottle, and perform cell centrifugation at a speed of 1000 rpm for 2 minutes. After centrifugation, pour out the supernatant, blow the centrifuged cells with 10 mL of cell culture medium, transfer the cell suspension to the well plate at 100 μL / well, seed it on the surface of the polymer fiber membrane material, and then add 900 μL of cell culture medium to each well. Place the seeded 24-well plate in the cell culture incubator. The first day after seeding is recorded as 0d, and the time starts from 0d. In the cell proliferation experiment of the fiber membrane, the cells proliferating on the blank group (not seeded on the polymer fiber membrane), the polymer fiber membrane without deposited bioactive material particles in Comparative Example 3, the polymer fiber membrane with uniform density deposited pure collagen particles in Comparative Example 2, the polymer fiber membrane with gradient density deposited pure collagen particles in Comparative Example 1, and the polymer fiber membrane with gradient density deposited growth factor particles in Example 1 need to be tested for absorbance (OD) value at 1d, 3d, 5d, and 7d. For all materials, the wells not participating in the test are replaced with the medium at 1d, 3d, 5d, and 7d. After the original culture medium is removed from each well, 1mL of cell culture medium is added; for the wells participating in the test, the CCK-8 test is performed. After the original culture medium is removed from each well, a CCK-8 solution obtained by mixing the cell culture medium and 10% of its volume of CCK-8 reagent is prepared and added thereto at 500μL / well. After 4 hours of placing the well plate in a cell culture incubator, test its OD value at a wavelength of 450nm. The OD value reflects the cell proliferation and is proportional to the number of cells. The test results are as follows Figure 5 As shown in the figure, the OD value increases with the number of days, indicating that cells proliferate on the material, cells can adhere to and grow on the fibers, the cells grow well, and the cell morphology is distinct, proving the excellent biocompatibility of the material. Figure 5 It can be seen from Example 1 that the density gradient signal and the deposition of growth factors on the fiber membrane have a promoting effect on cell proliferation.
Claims
1. A staged release rigid-flexible composite nerve conduit, with a polymer fiber membrane as the tube wall and a multi-segment hydrogel as the inner core, the inner wall of the polymer fiber membrane is deposited with biologically active material particles containing growth factors, and the multi-segment hydrogel includes a short-segment hydrogel containing anti-inflammatory substances and a long-segment hydrogel containing growth factors.
2. The rigid-flexible composite nerve conduit according to claim 1, characterized in that: The polymer fiber membrane is a double-layer nanofiber membrane structure, wherein the inner layer is a unidirectional orderly arranged nanofiber membrane, and the outer layer is a randomly arranged nanofiber membrane; and / or, The polymer in the polymer fiber is selected from at least one of degradable aliphatic polyesters, preferably at least one of polylactic acid, polycaprolactone, polylactic acid-glycolic acid copolymer, polylactic acid-glycolic acid-caprolactone copolymer; and / or, The anti-inflammatory substance is selected from at least one of catalase, superoxide dismutase, interleukin, and reducing molecules; and / or, The growth factor is selected from at least one of vascular endothelial growth factor, fibroblast growth factor, epidermal growth factor, brain-derived neurotrophic factor, neurotrophin-3, glial cell-derived neurotrophic factor, ciliary neurotrophic factor, and nerve growth factor; and / or, The hydrogel precursor compound used in the hydrogel is selected from at least one of acrylated biomacromolecules, preferably at least one of methacrylated gelatin, methacrylated hyaluronic acid, methacrylated silk fibroin, methacrylated chitosan, and methacrylated sodium alginate; and / or, The bioactive substance particles containing growth factors are of a core-shell structure, wherein the shell layer is the bioactive substance and the core layer is the growth factor; and / or, The bioactive substance is selected from at least one of protein compounds, preferably at least one of collagen, laminin, fibronectin and collagen.
3. The rigid-flexible composite nerve conduit according to claim 1, characterized in that: The thickness of the polymer fiber membrane tube wall is 50 to 800 μm, preferably 100 to 500 μm; and / or, The length ratio of the short-segment hydrogel to the long-segment hydrogel is 1:(1.5-10), preferably 1:(1.5-5); and / or, The cross-linking degree of the short-segment hydrogel is lower than that of the long-segment hydrogel.
4. A method for preparing the phased-release rigid-flexible composite nerve conduit according to any one of claims 1 to 3, comprising: The hydrogel precursor solution containing anti-inflammatory substances and the hydrogel precursor solution containing growth factors are cross-linked by ultraviolet light to obtain multi-segment hydrogels, and then the multi-segment hydrogels are wrapped with a polymer fiber membrane with biologically active substance particles containing growth factors deposited on the inner layer to obtain the staged release rigid-flexible composite nerve conduit.
5. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: Step (1) electrospinning the polymer solution A to obtain a double-layer polymer fiber membrane; Step (2) using coaxial electrostatic spraying of the growth factor solution B and the bioactive substance solution C to the inner layer of the polymer fiber membrane obtained in step (1) to prepare a polymer fiber membrane with gradient density deposited bioactive substance particles; Step (3) respectively mixing the growth factor solution D and the anti-inflammatory substance solution E with the initiator to obtain the initiator solution F and the initiator solution G, and then respectively adding the hydrogel precursor compound to obtain the hydrogel precursor solution H and the hydrogel precursor solution I; Step (4) injecting the hydrogel precursor solution H into the mold, crosslinking it with ultraviolet light, and then continuously injecting the hydrogel precursor solution I, crosslinking it with ultraviolet light, to obtain a multi-segment hydrogel; Step (5) contacting the inner layer of the polymer fiber membrane with gradient density deposited bioactive material particles obtained in step (2) with the multi-segment hydrogel obtained in step (4), wrapping them into a tube, and finally bonding them with polymer solution A to obtain the staged release rigid-flexible composite nerve conduit.
6. The preparation method according to claim 5, characterized in that: In the step (1): The solvent in the polymer solution A is selected from at least one of hexafluoroisopropanol, trifluoroethanol, chloroform, methanol, dichloromethane and N,N'-dimethylformamide; and / or, The mass percentage concentration of the polymer solution A is 5 to 25%, preferably 8 to 15%; and / or, The electrospinning comprises: performing uniaxial electrospinning on a polymer solution A, using a roller or a U-shaped groove as a receiver, the spinning solution flow rate is 0.1 to 3 mL / h, the voltage is 10 to 20 kV, and the receiving distance is 10 to 20 cm; preferably, when the electrospinning uses a roller as a receiver, the high-speed rotating roller is first used as a receiver to spin for 2 to 10 hours to obtain a unidirectional ordered fiber membrane, and then the roller speed is reduced to spin for 2 to 10 hours; or, when the electrospinning uses a U-shaped groove as a receiver, the U-shaped groove is first used as a receiver to spin for 2 to 10 hours to obtain a unidirectional ordered fiber membrane, and then the U-shaped groove is removed, and the unidirectional ordered fiber membrane obtained is used as a collector to spin for 2 to 10 hours.
7. The preparation method according to claim 5, characterized in that: In the step (2): The solvent in the growth factor solution B is selected from at least one of phosphate buffered saline, water, ethanol, polyvinyl alcohol, polyacrylamide, and polyacrylic acid; and / or, The concentration of the growth factor solution B is 0.1 μg / mL to 5 mg / mL, preferably 1 μg / mL to 1 mg / mL; and / or, The solvent in the bioactive substance solution C is selected from at least one of hydrochloric acid, acetic acid aqueous solution, ethyl acetate, glycerol, trifluoroethanol, and hexafluoroisopropanol; and / or, The concentration of the bioactive substance solution C is 1 to 50 mg / mL, preferably 10 to 30 mg / mL; and / or, The coaxial electrostatic spraying comprises: using a mask pattern to deposit bioactive substance particles in a gradient increasing manner along the direction of orderly fiber arrangement, injecting a bioactive substance solution C into a shell layer syringe, and injecting a growth factor solution B into a core layer syringe, the inner layer of the polymer fiber membrane obtained in step (1) is used as a receiver, the flow rate of the shell layer electrospraying solution is 0.5 to 3 mL / h, the flow rate of the core layer electrospraying solution is 0.2 to 1 mL / h, the voltage is 10 to 20 kV, the receiving distance is 10 to 20 cm, and the electrostatic spraying time is 1 to 60 minutes.
8. The preparation method according to claim 5, characterized in that: In the step (3): The solvent in the growth factor solution D is selected from at least one of phosphate buffered saline, water, ethanol, polyvinyl alcohol, polyacrylamide, and polyacrylic acid; and / or, The concentration of the growth factor solution D is 0.1 μg / mL to 5 mg / mL, preferably 1 μg / mL to 1 mg / mL; and / or, The solvent in the anti-inflammatory substance solution E is selected from at least one of phosphate buffered saline, water, chloroform, glycerol, trifluoroethanol, and hexafluoroisopropanol; and / or, The concentration of the anti-inflammatory substance solution E is 1 μg / mL to 5 mg / mL, preferably 0.1 to 2 mg / mL; and / or, The initiator in the initiator solution F and the initiator in the initiator solution G are independently selected from at least one of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, and ethyl 2,4,6-trimethylbenzoylphenylphosphonate; and / or, The mass percentage of the initiator in the initiator solution F is 0.1 to 0.5%, preferably 0.15 to 0.3%; and / or, The mass percentage of the initiator in the initiator solution G is 0.1 to 0.5%, preferably 0.15 to 0.3%; and / or, The mass percentage of the hydrogel precursor compound in the hydrogel precursor solution H is 5 to 15%, preferably 8 to 12%; and / or, The mass percentage of the hydrogel precursor compound in the hydrogel precursor solution I is 5 to 15%, preferably 8 to 12%.
9. The preparation method according to claim 5, characterized in that: In the step (4): The mold is a tubular mold; and / or, The conditions for the ultraviolet crosslinking are: the crosslinking temperature is 18 to 37° C., preferably 20 to 30° C.; the crosslinking time is 4 to 60 seconds, preferably 4 to 30 seconds.
10. Use of the phased-release rigid-flexible composite nerve conduit according to any one of claims 1 to 3 or the phased-release rigid-flexible composite nerve conduit obtained by the preparation method according to any one of claims 4 to 9 in bio-based repair materials.
Citation Information
Patent Citations
Collagen preparation for the controlled release of active substances
CA2188464A1
Preparation method of tissue engineering scaffold for realizing time-ordered release of medicine
CN103611187A
Nerve conduit loaded with gradient density particles and preparation method
CN114788892A
Bone repair material for promoting osteoblast generation and preparation method thereof
CN116139344A
Biomedical gel with tumor ablation and bone defect repair functions and preparation method of biomedical gel
CN116459391A
Cited By
Nerve conduit and preparation method thereof
CN120939292A
Nerve conduits and their preparation methods
CN120939292B